Original Research: Hydroxytyrosol, an ingredient of olive oil, reduces triglyceride accumulation and promotes lipolysis in human primary visceral adipocytes during differentiation. Issue 16 (October 2016) - Stefanon, Bruno; Colitti, Monica
Hydroxytyrosol has various pharmacological properties, including anti-oxidative stress and anti-inflammatory activities, preventing hyperglycemia, insulin resistance, and the metabolic syndrome. The present study is focused on the anti-adipogenic and lipolytic activity of hydroxytyrosol on primary human visceral adipocytes. Pre-adipocytes were analyzed after 10 (P10) and 20 (P20) days of treatment during differentiation and after 7 (A7) days of treatment when they reached mature shape. The treatment with hydroxytyrosol extract significantly ( P  < 0.001) increased apoptosis in P10 and P20 cells in comparison to control and A7 cells; significantly ( P  < 0.001) reduced triglyceride accumulation in P20 cells compared to P10 and control cells; and significantly ( P  < 0.001) increased lipolysis in P20 cells in comparison to control cells and A7 mature adipocytes. Hydroxytyrosol-treated P20 cells significantly ( P  < 0.05) increased expression of genes involved in inhibition of adipogenesis, such as GATA2, GATA3, WNT3A, SFRP5, HES1, and SIRT1. In contrast, genes involved in promoting adipogenesis such as LEP, FGF1, CCND1, and SREBF1 were significantly down-regulated by hydroxytyrosol treatment. These data suggest that hydroxytyrosol promotes lipolysis and apoptotic activity in primary human visceral pre-adipocytes during differentiation and does not affect already mature adipocytes.